CHANGES IN TAXATIONRULES AND ITS IMPACT ON CORPORATE FINANCIAL MANAGEMENT - Mega Arum; Dwi Fitrianingsih; Indra Sulistiana (Journal of Industrial Engineering & Management Research, 2025)
Changes in tax regulations are one of the significant external factors in the business environment that can influence a company's financial management. New tax rules often have broad implications for companies, both in terms of costs and financial strategy. These changes may involve adjustments to tax rates, changes in incentive policies, and updates to tax procedures and reporting. The impact on a company's financial management can vary, from changes in budget planning, cash management, to investment strategies. Companies need to make adjustments in their financial strategies to optimize tax obligations and take advantage of existing incentives. In addition, changes in tax regulations can also influence long-term strategic decisions, such as decisions to expand, restructure or diversify a business. This research aims to analyze the impact of changes in tax regulations on company financial management, with a focus on how companies respond to these changes and what strategies are implemented to minimize risks and maximize opportunities. This analysis uses a qualitative approach with case studies on several different companies, to provide a comprehensive picture of the practical implications of changes to tax regulations. It is hoped that the research results will provide insight for financial practitioners and policy makers in formulating effective strategies in dealing with changes in the tax environment